Investigation of the inhibitory mechanism of apomorphine against MDM2–p53 interaction. Issue 11 (1st June 2017) - Ishiba, Hiroyuki; Noguchi, Taro; Shu, Keitou; Ohno, Hiroaki; Honda, Kaori; Kondoh, Yasumitsu; Osada, Hiroyuki; Fujii, Nobutaka; Oishi, Shinya
Graphical abstract: Abstract: Mirror-image screening usingd -proteins is a powerful approach to provide mirror-image structures of chiral natural products for drug screening. During the course of our screening study for novel MDM2–p53 interaction inhibitors, we identified that NPD6878 ( R -(−)-apomorphine) inhibited both the nativel -MDM2–l -p53 interaction and the mirror-imaged -MDM2–d -p53 interaction at equipotent doses. In addition, both enantiomers of apomorphine showed potent inhibitory activity against the native MDM2–p53 interaction. In this study, we investigated the inhibitory mechanism of both enantiomers of apomorphine against the MDM2–p53 interaction. Achiral oxoapomorphine, which was converted from chiral apomorphines under aerobic conditions, served as the reactive species to form a covalent bond at Cys77 of MDM2, leading to the inhibitory effect against the binding to p53.